Emotions against images. : Motive and meaning of symbolic attacks towards 19th Century sculptures. Pre-democratic action? - Zozaya-Montes, Maria (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In the 21st century and especially during the Covid-19 pandemic, a wave of attacks against sculptures whose past revealed colonialism, racism or slave exploitation erupted in Europe and America. The attacks evidenced the persistence of a monumental heritage that represented symbols of oppression, and that questioned the representation of human rights. This study explores several historical backgrounds and current cases to analyze the nature and underlying motives of this type of symbolic vandalism.